Incidence of Thyroid Cancer in Thyroid Swelling, Study of 200 Cases - Matin, MA; Islam, Mohammad Saiful; Razzak, Md Abdur; Khanam, Mohosana; Harun, Md Abdullah Al; Kabir, Shahjahan; Saifuddin, AKM; Sobhan, AKMA (Bangladesh Journal of Otorhinolaryngology, 2021)
Objective: The incidence of thyroid cancer has rapidly increased in the United States (US) and other developed countries over the past 30 years but there is no study to find out the true incidence of thyroid cancer in Bangladesh. The aim of this study is to compare FNAC with histopathology reports and to find out the true incidence of thyroid malignancy in thyroidectomy patients presenting with thyroid swelling. Methods: This is a prospective study of 200 thyroid swelling patients underwent thyroid surgery done at Shaheed Suhrawardy Medical College Hospital, a tertiary Care Hospital in Dhaka from July 2017 to December 2020. FNAC and histopathology reports were studied to find out the incidence of benign and thyroid malignancy among the thyroid swelling. Results: The age of the patients ranged from 8 to 75 years. The mean age was 37.2 years. There were 156 female and 44 male patients with female male ratio 3.54:1. Diagnostic categorization of 200 thyroid swelling underwent surgery, FNAC based on Bathesda classification showed that 163 (81.5%) cases were cytologically benign, 37 (18.5%) cases were malignant category. Out of 200 cases histopathology showed134 cases(67.0%) are benign and 66(33.0%) are malignant thyroid swelling. Among the benign lesions96.31% are colloid goiter and among the malignant lesions 93.4% are papillary thyroid carcinoma. Conclusion: Although FNAC is an essential diagnostic test to rule out thyroid malignancy but histopathological examination is the only way to give true incidence of thyroid malignancy among the thyroid swelling and it is observed that there is high incidence of thyroid malignancy(33.0%) among the thyroid swelling patient underwent thyroid surgery. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 12-16